2013
DOI: 10.1007/s00404-013-3080-9
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of tumor necrosis factor-stimulated gene-6 (TSG-6) expression in human endometrium

Abstract: These data suggest that TSG-6 expression might be essential in endometrial matrix organization and feto-maternal communication during the implantation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…37 TNFAIP6 protein is a secreted protein which belongs to a member of the hyaluronic acid-binding protein family, and it may be related to the stability of extracellular matrix and cell migration. 38,39 Physiological Functions and Mechanisms of TNFAIP6 TSG-6 is believed to be an inflammatory protein associated with accelerated wound healing and reduced tissue fibrosis, and it can regulate chemokines by inhibiting the interaction of chemokines and mucopolysaccharides. 40,41 In rheumatoid arthritis and osteoarthritis, a study found that TSG-6 was high expression in patients' joints, suggesting that TSG-6 might be a proinflammatory medium.…”
Section: Tnfaip6 Basic Characteristics Of Tnfaip6mentioning
confidence: 99%
See 1 more Smart Citation
“…37 TNFAIP6 protein is a secreted protein which belongs to a member of the hyaluronic acid-binding protein family, and it may be related to the stability of extracellular matrix and cell migration. 38,39 Physiological Functions and Mechanisms of TNFAIP6 TSG-6 is believed to be an inflammatory protein associated with accelerated wound healing and reduced tissue fibrosis, and it can regulate chemokines by inhibiting the interaction of chemokines and mucopolysaccharides. 40,41 In rheumatoid arthritis and osteoarthritis, a study found that TSG-6 was high expression in patients' joints, suggesting that TSG-6 might be a proinflammatory medium.…”
Section: Tnfaip6 Basic Characteristics Of Tnfaip6mentioning
confidence: 99%
“…40 In vitro studies found that TSG-6 interacted with protein ligands and different mucopolysaccharides, and it could inhibit neutrophilic migration. 39 In addition, TSG-6 could inhibit the transmigration of neutrophils stimulated by chemokines through direct interaction between TSG-6 and CXCL8 binding site. At the same time, TSG-6 might impair the binding of CXCL8 to cell surface mucopolysaccharide, as well as the transport of CXCL8 in endothelial cells.…”
Section: Tnfaip6 Basic Characteristics Of Tnfaip6mentioning
confidence: 99%
“…TSG6 is released from neutrophils, mast cells, macrophages, and stromal cells, and it displays antiinflammatory and tissue-protective properties (Day and Milner, 2019). These include inhibition of neutrophil migration, polarization of macrophages to an anti-inflammatory M2 phenotype, and modulation of endometrial matrix turnover and organization (Capp et al, 2014;Day and Milner, 2019). The present results lead to the hypothesis that underexpression of TSG6 in ST cells of persistent cows may be a relevant marker for the persistence of endometrial inflammation or a putative therapeutic target.…”
Section: Endometrial Health Status and Genes Related To Immune Responsementioning
confidence: 54%
“…During MeV infection, viral P protein activates the expression of the ubiquitin modifier TNFAIP3, which interacts with TRAF6-binding protein, TAX1BP1, forming a complex that acts as TRAF6 inhibitor by preventing E3 ligase TRAF6 polyubiquitination [ 63 ], thus blocking the TLR4-mediated proinflammatory signaling [ 63 ]. The second member of the family found to be overexpressed in our study is TNFAIP6, known as TSG-6, a secreted multifunctional protein, produced at sites of inflammation, which acts as mediator of tissue remodeling and anti-inflammatory responses, mainly by regulating chemokines [ 61 , 64 , 65 ]. Human TNFAIP6 has a Link module (Link_TSG6) which binds to CXC- and CC-chemokines inhibiting neutrophile migration and their influx to inflammatory sites [ 64 ].…”
Section: Discussionmentioning
confidence: 99%